2021
DOI: 10.3390/md19090487
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology of Native Fucosylated Glycosaminoglycans and the Safety of Their Depolymerized Products as Anticoagulants

Abstract: Fucosylated glycosaminoglycan (FG) from sea cucumber is a potent anticoagulant by inhibiting intrinsic coagulation tenase (iXase). However, high-molecular-weight FGs can activate platelets and plasma contact system, and induce hypotension in rats, which limits its application. Herein, we found that FG from T. ananas (TaFG) and FG from H. fuscopunctata (HfFG) at 4.0 mg/kg (i.v.) could cause significant cardiovascular and respiratory dysfunction in rats, even lethality, while their depolymerized products had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Notably, a recent study reported that 4.0 mg/kg (i.v.) of FGs (derived from Thelenota ananas and Holothuria fuscopunctata) could cause significant cardiovascular and respiratory dysfunction in rats which was mainly ascribed to pulmonary microvessel embolism due to platelet aggregation and contact activation-mediated coagulation, while their depolymerized products (dTaFG13 and dHG-5) had no obvious side effects (Lin et al, 2021). Yin et al (2021) purified the Compounds 5 from the depolymerized natural Glycosaminoglycans of sea cucumber Thelenota ananas and tested its anticoagulant activity in mice and antithrombotic activity in rat model.…”
Section: Fucosylated Glycosaminoglycanmentioning
confidence: 99%
“…Notably, a recent study reported that 4.0 mg/kg (i.v.) of FGs (derived from Thelenota ananas and Holothuria fuscopunctata) could cause significant cardiovascular and respiratory dysfunction in rats which was mainly ascribed to pulmonary microvessel embolism due to platelet aggregation and contact activation-mediated coagulation, while their depolymerized products (dTaFG13 and dHG-5) had no obvious side effects (Lin et al, 2021). Yin et al (2021) purified the Compounds 5 from the depolymerized natural Glycosaminoglycans of sea cucumber Thelenota ananas and tested its anticoagulant activity in mice and antithrombotic activity in rat model.…”
Section: Fucosylated Glycosaminoglycanmentioning
confidence: 99%
“…Sulfated polysaccharides employed for some applications can cause in some cases adverse effects, that are associated with high molecular weight sulfated species (Fonseca et al, 2010;Lin et al 2021), Therefore, HE800 EPS produced by V. diabolicus HE800 fermentation under controlled conditions, was partially depolymerized through a H 2 O 2 -mediated free radical reaction to give a LMW HE800 EPS (approx. 24 kDa, Table 1) before any sulfate group insertion.…”
Section: Semi-synthesis Of Gag-like Sulfated Polysaccharides From Lmw...mentioning
confidence: 99%
“…GAGs are involved in various biological processes, such as cell signaling [1] and extracellular matrix assembly. Due to their unique biological properties, there has been a burgeoning interest in glycosaminoglycans for medical use as coating materials for anti-inflammatory agents [2] , [3] and anticoagulants [4] , [5] . A review about the development of GAG applications in medicine and pharmacy has been published recently [6] .…”
Section: Introductionmentioning
confidence: 99%